OP0103 The effect of sirukumab plus methotrexate on circulating biomarkers of joint destruction in moderate to severe rheumatoid arthritis patients from the sirround-d phase 3 study. (15th June 2017) - Dasgupta, B; Campbell, K; Bay-Jensen, A-C; Karsdal, M; Sweet, K; Sims, M; Loza, MJ
Abstract : Background: Rheumatoid arthritis (RA) is an autoimmune disease characterized by chronic inflammation that can lead to progressive bone and joint damage. The cytokine interleukin-6 (IL-6) is implicated in inflammatory pathways associated with bone and cartilage degradation in RA. Inhibition of IL-6 signaling by sirukumab (SIR), an anti-IL6 cytokine monoclonal antibody, was shown to significantly reduce structural damage progression, relative to placebo (pbo), in disease-modifying antirheumatic drug inadequate responder (DMARD-IR) RA patients (pts) in the Phase 3 SIRROUND-D study. Objectives: To investigate the mechanism of SIR on joint tissue remodeling, a panel of serum biomarkers associated with matrix metalloproteinase (MMP)-driven interstitial matrix and basement membrane degradation (C1M, C3M, C4M), bone turnover (β-isomerized C-terminal telopeptides of type I collagen, CTX-I), osteoblast formation (osteocalcin/NMID), synovial destruction (MMP-3), and tissue inflammation (MMP-mediated destruction of CRP/CRPM) were assessed in pts with moderate to severe RA from SIRROUND-D. Methods: Serum samples from a sub-cohort of SIRROUND-D (for whom radiographic data were available) were analyzed ad hoc for the following biomarkers: C1M, C3M, C4M, CRPM, MMP-3, CTX, and osteocalcin. Samples from 100 pts treated with pbo and methotrexate (MTX) and 100 pts treated with SIR 50mg q4w + MTX were tested. Biomarkers were measured in all pts at baseline (BL) and Wk 4; samples from SIR and pbo-treated pts (50/group) were tested at Wk 52. Differences between groups were evaluated by comparing within-subject log2 ratio of Wk 4 or Wk 52 over BL values between treatment groups. Structural damage progressors versus non-progressors were defined based on changes from BL in Sharp/van der Heijde score (SHS) at Wk 52 (≥5 vs <5). Differences between groups were tested using General Linear Models. Results: SIR significantly reduced serum levels of C1M (-48%), C3M (-30%), C4M2 (-42%), and CRPM (-22%) by Wk 4 vs pbo ( P <0.001), with similar reductions observed at Wk 52; MMP-3 levels were more substantially decreased by SIR at Wk 52 (-39%) vs Wk 4 (-20%). In contrast, treatment with SIR resulted in increased levels of CTX-I (+20%) and osteocalcin (+12%) by Wk 4 ( P <0.001; Figure 1 ). As 95% of the total study population included in this biomarker analysis did not progress (defined as ≥5 Wk 52 change in SHS), we were unable to demonstrate an association between changes in pharmacodynamic markers and radiographic progression. Nor were significant associations with pharmacodynamic changes with SIR treatment observed for comparisons among patients grouped by Wk 52 changes in SHS of ≥5 (n=5), <5 to ≥0.5 (n=41), and <0.5 (n=51). BL or Wk 4 changes in levels of individual analytes were not associated with Wk 24 ACR50 or DAS28-CRP responses. Conclusions: SIR 50mg q4w + MTX, vs pbo + MTX, inhibited radiographic progression in RA pts in SIRROUND-D and strongly inhibited biomarkers of joint and tissue destruction while enhancing markers of bone formation. These data suggest SIR may actively suppress inflammatory pathways implicated in joint destruction in RA pts. Disclosure of Interest: B. Dasgupta Employee of: Janssen Research & Development, LLC, K. Campbell Employee of: Janssen Research & Development, LLC, A.-C. Bay-Jensen Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, M. Karsdal Shareholder of: Nordic Bioscience, Employee of: Nordic Bioscience, K. Sweet Employee of: Janssen Research & Development, LLC, M. Sims Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, M. Loza Employee of: Janssen Research & Development, LLC